Pengaruh Debt To Equity Ratio Dan Total Asset Turnover Terhadap Nilai Perusahaan (Study Kasus Perusahaan Sektor Otomotif Yang Terdaftar Di Bei Tahun 2016-2019) - Doni Pranata; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to identify the influence of DER and TATO on firm value (case study of automotive sector companies listed on the IDX in 2016-2019). The analytical method used in this research is multiple linear regression analysis which includes classical assumption test analysis and hypothesis testing. The population in this study were 15 companies in the automotive sector listed on the IDX in 2016-2019. In this study, the sample used a purposive sampling method, in order to obtain 10 companies that meet the criteria in the automotive sector companies. The results of this study indicate that (1) Debt to equity ratio and total asset turnover simultaneously have a positive effect on price to book value. (2) The ratio of debt to partial equity has no effect on book price to value. (3) Partially total asset turnover has a positive effect on price book to value. Keywords: Total asset turnover, price to book value, debt to equity ratio